2000
DOI: 10.1177/229255030000800502
|View full text |Cite
|
Sign up to set email alerts
|

Dupuytren's Disease in Saudi Arabia

Abstract: In a prospective study, 600 consecutive adult Saudi patients were examined for clinical evidence of Dupuytren's disease. Dupuytren's disease was found in two of the 600 patients (0.003%). Both patients were native Saudi. Predisposing factors and clinical findings were reported for both cases. It was concluded that Dupuytren's disease is extremely rare among Saudi Arabians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(1 reference statement)
0
0
0
Order By: Relevance
“…The reported prevalence of DD varies from 2% to 42%, influenced mainly by ethnicity, gender, and age [ 1 ]. Numerous studies [ 1 , 5 , 9 ] have consistently reported an age-related increase in the prevalence of DD, with a higher occurrence in males and individuals of Northern European descent. Surprisingly, a 2020 study identified the highest DD rate in Africa at 17.2%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported prevalence of DD varies from 2% to 42%, influenced mainly by ethnicity, gender, and age [ 1 ]. Numerous studies [ 1 , 5 , 9 ] have consistently reported an age-related increase in the prevalence of DD, with a higher occurrence in males and individuals of Northern European descent. Surprisingly, a 2020 study identified the highest DD rate in Africa at 17.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, subgroup analysis demonstrated the greatest prevalence among patients with type 1 diabetes, reaching 34.1% [ 4 ]. In addition, a prospective study involving 600 adult Saudi patients revealed a remarkably low detection of DD in only two individuals (0.003%), both of Saudi descent, highlighting the rarity of DD in Saudi Arabians [ 9 ].…”
Section: Introductionmentioning
confidence: 99%